Tomm34 is commonly expressed in epithelial ovarian cancer and associates with tumour type and high FIGO stage - Muller, Petr; Coates, Philip J; Nenutil, Rudolf; Trcka, Filip; Hrstka, Roman; Chovanec, Josef; Brychtova, Veronika; Vojtesek, Borivoj (Journal of ovarian research, 2019)
BACKGROUND: Increased activity of the chaperones Hsp70 and Hsp90 is a common feature of solid tumours. Translocase of the outer mitochondrial membrane 34 (Tomm34) is a cochaperone of both Hsp70 and Hsp90 that was found to be overexpressed in colorectal, hepatocellular, lung and breast carcinomas. The expression profile of Tomm34 in ovarian cancer has not been investigated. Therefore, the aim of the current study was to investigate the expression pattern of Tomm34 in ovarian carcinomas and analyse its correlation with clinico-pathological parameters. RESULTS: Epithelial ovarian cancers (140) were histologically classified based on their morphology and graded into two types comprising 5 histologic subgroups. Type I carcinomas comprise low grade serous (LGSC), clear cell (CCOC) and endometrioid (ENOC), type II comprises high grade serous carcinomas (HGSC) and solid, pseudoendometrioid, transitional carcinomas (SET). Tomm34 was more highly expressed in type II than type I carcinomas (p < 0.0001). Comparing tumours based on the mutation in the TP53 gene revealed similar results, where mutant tumours exhibited significantly higher levels of Tomm34 (p < 0.0001). The decreased levels of Tomm34 in type I carcinomas were particularly evident in clear cell and mucinous carcinomas. The expression of Tomm34 was also positively correlated with FIGO stage (r = 0.23; p = 0.007). Tomm34 levels also indicated poor prognosis for patients with mutant p53. CONCLUSIONS: Our data indicate that Tomm34 is commonly expressed at high levels in epithelial ovarian cancers, except for the clear cell and mucinous subtypes. The expression of Tomm34 corresponds with the dualistic model of ovarian cancer pathogenesis where high grade, type II tumours exhibit higher expression of Tomm34 in contrast to type I tumours. These data are also comparable to the previous findings that Tomm34 is a marker of progression and poor prognosis in human cancer.
Keywords: transportní proteiny mitochondriální membrány; Humans; lidé středního věku; Disease Progression; Biomarkers, Tumor; nádorový supresorový protein p53; Female; mutace; Aged; dospělí; nádory vaječníků; Ovarian Neoplasms; senioři; lidé; Immunohistochemistry; imunohistochemie; nádorové biomarkery; Carcinoma, Ovarian Epithelial; Adult; epiteliální ovariální karcinom; staging nádorů; ženské pohlaví; Middle Aged; prognóza; Aged, 80 and over; senioři nad 80 let; progrese nemoci; Neoplasm Staging; Mitochondrial Membrane Transport Proteins; Mutation; Prognosis; Tumor Suppressor Protein p53